2011
DOI: 10.1186/cc10061
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of early versus late initiation of renal replacement therapy in critically ill patients with acute kidney injury: a systematic review and meta-analysis

Abstract: IntroductionOur aim was to investigate the impact of early versus late initiation of renal replacement therapy (RRT) on clinical outcomes in critically ill patients with acute kidney injury (AKI).MethodsSystematic review and meta-analysis were used in this study. PUBMED, EMBASE, SCOPUS, Web of Science and Cochrane Central Registry of Controlled Clinical Trials, and other sources were searched in July 2010. Eligible studies selected were cohort and randomised trials that assessed timing of initiation of RRT in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
268
5
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 385 publications
(292 citation statements)
references
References 46 publications
6
268
5
13
Order By: Relevance
“…24,25 In the absence of data from suitably powered randomized trials, a recent systematic review comparing 'early' to 'late' initiation of RRT for AKI concluded that there was insufficient evidence to guide practice. 26 Uncertainty about the optimal timing of RRT initiation for critically ill patients with AKI likely contributes to practice variation, which may affect patient outcomes. Accordingly, we conducted a multicentre prospective observational study to describe current practice patterns in Canada with respect to the timing of, and indications for, initiation of RRT in critically ill patients with AKI.…”
Section: Résumémentioning
confidence: 99%
“…24,25 In the absence of data from suitably powered randomized trials, a recent systematic review comparing 'early' to 'late' initiation of RRT for AKI concluded that there was insufficient evidence to guide practice. 26 Uncertainty about the optimal timing of RRT initiation for critically ill patients with AKI likely contributes to practice variation, which may affect patient outcomes. Accordingly, we conducted a multicentre prospective observational study to describe current practice patterns in Canada with respect to the timing of, and indications for, initiation of RRT in critically ill patients with AKI.…”
Section: Résumémentioning
confidence: 99%
“…Deux grandes méta-analyses concluent qu'une recommandation définitive sur le TRR précoce doit attendre les résultats d'une grande étude contrôlée prospective. 5,6 Les deux méta-analyses ont montré un avantage statistique en faveur du TRR précoce, mais les auteurs ont signalé que les études existantes sont essentiellement rétrospectives et hétérogènes, et qu'elles utilisent des définitions variables de « précoce ».…”
Section: Orunclassified
“…Two large metaanalyses conclude that a definitive recommendation on early RRT must await a large prospective controlled trial. 5,6 Both meta-analyses showed a statistical benefit for early RRT, but their authors pointed out that existing studies are mostly retrospective and heterogeneous and use variable definitions for ''early''.…”
mentioning
confidence: 99%
“…The majority of published studies have been retrospective or nonrandomized observational cohorts. Meta-analyses of these studies have suggested that earlier initiation of renal support is associated with lower mortality (4-6) and a trend toward greater recovery of kidney function (4). Interpretation of these data must be tempered, however, by the failure to include patients with early AKI who never initiated RRT, because they either recovered kidney function or died.…”
mentioning
confidence: 99%